Sosialisasi dan implementasi program smart village di Kecamatan Benai, Kabupaten Kuantan Singingi - Okta Karneli; Ruzikna Ruzikna; Kasmirudin Kasmirudin; Frini Karina Andini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Village development is currently experiencing significant has change in concepts and processing. Villlage development concept not just in agraris sector and base infrastructure, but has been pointing in information technology and communication development. Since 2018, internet network has come to this district, and become an oppourtunity for the community to use the smart internet and develop village potential and community business to increase the economics and prosperity. These are the focus of this coaching program. The method of this coacing program are description concept to use smart internet to increase the prosperity and economics, discuss the potential, problem and solution their problem and simulation for the practice. The result of this program are solve their problem about the ability and increase the community ability to use smart internet and their can develop their business to be more suistanable and can increase the prosperity.